Progressive changes in cerebral perfusion after carotid stenting: a dynamic susceptibility contrast perfusion weighted imaging study. (12th August 2013) - Piñero, Pilar; González, Alejandro; Moniche, Francisco; Martínez, Eva; Cayuela, Aurelio; González-Marcos, José-Ramón; Mayol, Antonio; Gil-Peralta, Alberto
Abstract : Background: We aimed to assess baseline inter-hemispheric perfusion differences, before carotid artery stenting (CAS), of severe internal carotid artery (ICA) stenosis, and to evaluate perfusion changes over time after CAS by means of perfusion weighted imaging (PWI). Methods: Dynamic susceptibility contrast PWI was performed in 33 patients with severe ICA stenosis 1 day before and 1 day after CAS, and repeated in 23 patients 30 days after CAS. Cerebral blood volume, cerebral blood flow, arrival time (T0), mean transit time, and time to peak (TTP) relative values comparing symptomatic and asymptomatic hemispheres before CAS were obtained. Pre- and post-CAS values were also compared in the treated hemisphere and middle cerebral artery (MCA) territories. The influence of collateral circulation and contralateral ICA stenosis were evaluated. Results: Before CAS, TTP was significantly increased in the affected hemisphere and MCA territory in all patients (p=0.007 and p=0.021, respectively). After treatment, normalization was observed for TTP and T0 30 days after CAS in all patients, mainly in patients with any grade of contralateral stenosis and with one or both functioning communicating arteries (42.4% of patients had both, and 42.4% showed only one—anterior communicating artery=11 patients (78.6%) and posterior communicating artery=3 patients (21.4%)). Conclusions: Inter-hemispheric perfusion differences in patients with severe ICA stenosis normalize after CAS in the long term, up to 30 days after the procedure.